CREDIT RISK AND ITS MANAGEMENT METHODS IN COMMERCIAL BANKS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The article deals with issues related to improving the management of credit risks in the activities of commercial banks of the Republic of Uzbekistan, as well as developed scientific proposals aimed at solving these problems. Also studied are further ways to improve monetary policy using the tools used in international best practice in the strategy of the President of the Republic of Uzbekistan.